Reviewing the Green Building Concepts Along With the Applications of AI and IoT for Environmental Monitoring and Designing Sustainable Infrastructures (Journal of Informatics and Mathematical Sciences, 2025)
This academic article explores the ever-evolving field of smart green building technologies, with a particular emphasis on the ways in which artificial intelligence (AI) and Internet of Things (IoT) are integrated into and affect sustainable architecture. The study is based on background of changing green building principles, which are highlighted by rapid development of smart technologies that are changing face of contemporary architecture. With goal of comprehending how AI and IoT might improve building performance and sustainability with simultaneous reduction in carbon footprints, the study takes a methodological approach that is based on a thorough assessment of the literature and qualitative analysis. It looks at how AI and IoT work together, how difficult it is to deploy them, how they affect society and environment, how much it will cost to invest in these technologies. The primary conclusions show that combining AI and IoT improves building performance, increases energy efficiency, promoting environmental sustainability. The study showcases cutting-edge IoT building management technologies and to create more sustainable and effective living environments. It also notes impediments to the uptake of these technologies, such as financial limitations and the requirement for highly qualified personnel. In summary, the study suggests a multimodal strategy to address these issues, with a focus on legislative changes, educational programs, and creation of affordable green building technologies. In-depth investigation of AI and IoT integration in sustainable building designs is presented in this study, along with insights into how these technologies may transform the construction sector and advance sustainable urban development.